Co-emergence and Collapse: The Mesoscopic Approach for Conceptualizing and Investigating the Functional Integration of Organisms - Bizzarri, Mariano; Giuliani, Alessandro; Pensotti, Andrea; Ratti, Emanuele; Bertolaso, Marta (Frontiers in Physiology, 2019)
The fall of reductionist approaches to explanation leaves biology with an unescapable challenge: how to decipher complex systems. This entails a number of very critical questions, the most basic ones being: ‘What do we mean by ‘complex’? and, ‘What is the system we should look for?’. In complex systems, constraints belong to a higher level that the molecular one and their effect reduces and constrains the manifold of the accessible internal states of the system itself. Function is related but not deterministically imposed by the underlying structure. It is quite unlikely that such kind of complexity could be grasped by current approaches focusing on a single organization scale. The natural co-emergence of systems, parts and properties can be adopted as a hypothesis-free conceptual framework to understand functional integration of organisms, including their hierarchical or multilevel patterns, and including the way scientific practice proceeds in approaching such complexity. External, ‘driving’ factors - order parameters and control parameters provided by the surrounding microenvironment - are always required to ‘push’ the components’ fate into well-defined developmental directions. In the negative, we see that in pathological processes such as cancer, organizational fluidity, collapse of levels and dynamic heterogeneity make it hard to even find a level of observation for a stable explanandum to persist in scientific practice. Parts and the system both lose their properties once the system is destabilized. The mesoscopic approach is our proposal to conceptualizing, investigating and explaining in biology. ‘Mesoscopic way of thinking’ is increasingly popular in the epistemology of biology and corresponds to looking for an explanation (and possibly a prediction) where ‘non-trivial determinism is maximal’: the ‘most microscopic’ level of organization is not necessarily the place where ‘the most relevant facts do happen’. A fundamental re-thinking of the concept of causality is also due for order parameters to be carefully and correctly identified. In the biological realm, entities have relational properties only, as they depend ontologically on the context they happen to be in. The basic idea of a relational ontology is that, in our inventory of the world, relations are somehow prior to the relata (i.e. entities).